Perturbation of 3D nuclear architecture, epigenomic aging and dysregulation, and cannabinoid synaptopathy reconfigures conceptualization of cannabinoid pathophysiology: part 2—Metabolome, immunome, synaptome - Reece, Albert Stuart; Hulse, Gary Kenneth (Frontiers in Psychiatry, 2023)
The second part of this paper builds upon and expands the epigenomic-aging perspective presented in Part 1 to describe the metabolomic and immunomic bases of the epigenomic-aging changes and then considers in some detail the application of these insights to neurotoxicity, neuronal epigenotoxicity and synpatopathy. Cannabinoids are well known to have bidirectional immunomodulatory activities on numerous parts of the immune system. Immune perturbations are well known to impact the aging process, the epigenome and intermediate metabolism. Cannabinoids also impact metabolism by many pathways. Metabolism directly impacts immune, genetic and epigenetic processes. Synaptic activity, synaptic pruning and thus the sculpting of neural circuits are based upon metabolic, immune and epigenomic networks at the synapse, around the synapse and in the cell body. Many neuropsychiatric disorders including depression, anxiety, schizophrenia, bipolar affective disorder and autistic spectrum disorder have been linked with cannabis. Therefore it is important to consider these features and their complex interrelationships in reaching a comprehensive understanding of cannabinoid dependence. Together these findings indicate that cannabinoid perturbations of the immunome and metabolome are important to consider alongside the well recognized genomic and epigenomic perturbations and it is important to understand their interdependence and interconnectedness in reaching a comprehensive appreciation of the true nature of cannabinoid pathophysiology. For these reasons a comprehensive appreciation of cannabinoid pathophysiology necessitates a coordinated multiomics investigation of cannabinoid genome-epigenome-transcriptome-metabolome-immunome, chromatin conformation and 3D nuclear architecture which therefore form the proper mechanistic underpinning for major new and concerning epidemiological findings relating to cannabis exposure.